Beyond preservation: investigating the roles of archivist. Issue 3 (3rd April 2017) - Vassilakaki, Evgenia; Moniarou-Papaconstantinou, Valentini
Abstract : Purpose: This paper aims to identify through a systematic review the roles that archivists adopt in a changing archival landscape and to illustrate any similarities between the roles of archivist and librarians. Design/methodology/approach: The systematic literature review approach was adopted for the purposes of this research. Specifically, peer-reviewed literature published in English between 2000 and 2015 was considered. The relevant papers were retrieved based on specific search terms run on related databases. Findings: The analysis showed that the traditional roles of record-keeper and collection manager were still relevant, whereas new ones, namely, digital archivist, archivist as educator and dual archivist/librarian, started to prevail. The technological developments as well as the social and educational changes seemed to have affected the emergence of these new roles, whereas the need for collaboration and communication among archivists, librarians and researchers was evident in many roles, namely, archivist as educator, dual archivist/librarian and archivist as researcher. Originality/value: This literature review explored the different roles that archivists adopt within their work context and not the archivists' skills, duties and responsibilities.